2017
DOI: 10.3389/fmed.2017.00133
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Spinal Anesthesia for Obstetric Anesthesia and Analgesia

Abstract: The widespread use of continuous spinal anesthesia (CSA) in obstetrics has been slow because of the high risk for post-dural puncture headache (PDPH) associated with epidural needles and catheters. New advances in equipment and technique have not significantly overcome this disadvantage. However, CSA offers an alternative to epidural anesthesia in morbidly obese women, women with severe cardiac disease, and patients with prior spinal surgery. It should be strongly considered in parturients who receive an accid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…As a result, the block is well predicted and tends to cause less hemodynamic perturbations [11,12]. Hence, it forms the basis for usage of CSA in high-risk cases [11,13] and allows CSA to be still in the game and in par with SSA and CEA. CEA on the contrary provides a segmental neural blockade and requires high volumes of local anaesthetics (LA).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the block is well predicted and tends to cause less hemodynamic perturbations [11,12]. Hence, it forms the basis for usage of CSA in high-risk cases [11,13] and allows CSA to be still in the game and in par with SSA and CEA. CEA on the contrary provides a segmental neural blockade and requires high volumes of local anaesthetics (LA).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are rare possible complications associated with intrathecal catheterisation including meningitis, epidural or spinal abscess, hematoma, arachnoiditis, or cauda equina syndrome. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Spinal anesthesia[ 3 , 4 ] is a common method of anesthesia for cesarean section. In fact, many studies have shown that opioids plus local anesthetics can have many benefits, such as prolonging the time of intraoperative and postoperative analgesia[ 5 ], effectively inhibiting the traction reaction caused by surgery[ 6 ] and allowing more stable hemodynamics[ 7 ].…”
Section: Introductionmentioning
confidence: 99%